Study of evolution of three-dimensional porous structure in zeolite-templated carbons - Arsakay, Madi; Shen, Boyuan; Chen, Xiao; Xiong, Hao; Duisenova, Korlan; Fatkhulloev, Alisher; Vorndran, Carola; Yang, Guangwu; Annageldyyev, Bayrammuhammet; Lee, Sun Hwa; Seong, Won Kyung; Thommes, Matthias; et al. (Carbon, 2025)
The atomic-scale and near-atomic-scale local structures during zeolite-templated carbon (ZTC) growth are not well understood. Our study provides insights into the structural evolution from the early to later stages, and finally, the completed stages of growth (i.e., carbon deposition inside the zeolite pores) of Ca-exchanged FAU zeolite-templated carbon using acetylene as a carbon source, through integrated differential phase contrast (iDPC) STEM. We observed that the carbon contrast in the different Ca-FAU channels varies over a wide range at the beginning of the growth (growth times of 10- and 20-min), indicating that different channels have a different number of carbon atoms in this early stage, and that a complete network has not yet been formed. As the time exposure to acetylene is extended (to 60- and 180-min), samples are made that show a high contrast in all channels and carbon atoms are more uniformly distributed (and more uniformly at 180 min than 60 min). Furthermore, the combination of CO2 and Ar adsorption techniques provides a full pore size distribution and provides values for the inner and outer surface areas and volumes of the hollow carbon structure. These findings can help to better understand the structure of ZTCs at the atomic and near-atomic levels, which can be leveraged to enhance ZTC performance in existing applications and potentially enable their use in new applications.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Atomic resolution; Carbon; Gas adsorption; Integrated differential phase contrast scanning transmission electron microscopy (iDPC-STEM); Surface area; Zeolite; Zeolite-templated carbon